Paper knives, paper crowns : political prints in the Dutch Republic - Cilleßen, Wolfgang (Krannert Art Museum, University of Illinois Urbana-Champaign, 2022)
"Paper Knives, Paper Crowns: Political Prints in the Dutch Republic explores the myriad and complex visual strategies early modern Netherlandish printmakers used to memorialize historical events, lionize and demonize domestic and international leaders, and form consensus for collective action. Netherlandish printmakers experimented with graphic visual language in a daring and subversive fashion. They supplemented conventions and tropes inherited from medieval and Renaissance maps, city views, book illustrations, news prints, and polemical prints and established new forms of expression. While some of their prints employ visual puns and humor that even the illiterate could enjoy, others were captioned in Latin or French as well as Dutch, enticing educated elites across Europe to explore the relationship between text and image. Through mercantile and diplomatic channels, Dutch political prints transcended national and temporal boundaries to make a lasting impact. The catalogue essays present a comprehensive chronological arc and thematic overview, addressing multiple types of printmaking as well as the medium's relationship to other art forms, including "fine art" printmaking, painting, drawing, sculpture, and architecture. As such, the book engages deeply with art historical scholarship and studies of early modern political history and theory. The publication will demonstrate that methods of using images to comment upon, manage, and understand political life in practice today are indebted to the radical innovations of early modern printmakers in the Dutch Republic"--